2015
DOI: 10.1002/hep.28153
|View full text |Cite
|
Sign up to set email alerts
|

Primary prophylaxis of variceal bleeding in children and the role of MesoRex Bypass: Summary of the Baveno VI Pediatric Satellite Symposium

Abstract: Approaches to the management of portal hypertension and variceal hemorrhage in pediatrics remain controversial, in large part because they are not well informed by rigorous clinical studies. Fundamental biological and clinical differences preclude automatic application of approaches used for adults to children. On April 11-12, 2015, experts in the field convened at the first Baveno Pediatric Satellite Meeting to discuss and explore current available evidence regarding indications for MesoRex bypass (MRB) in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 62 publications
(195 reference statements)
1
97
0
10
Order By: Relevance
“…When symptoms associated with splenomegaly (abdominal pain and compression) or a tendency to bleed and severely decreased blood cells (at least one of the following: platelets, ≤5 × 10 4 ; white blood cells, ≤3000; and red blood cells, ≤300 × 10 4 ) associated with splenomegaly, partial splenic embolization or splenectomy should be considered …”
Section: Guidelines For Treatment Of Aberrant Portal Hemodynamicsmentioning
confidence: 99%
“…When symptoms associated with splenomegaly (abdominal pain and compression) or a tendency to bleed and severely decreased blood cells (at least one of the following: platelets, ≤5 × 10 4 ; white blood cells, ≤3000; and red blood cells, ≤300 × 10 4 ) associated with splenomegaly, partial splenic embolization or splenectomy should be considered …”
Section: Guidelines For Treatment Of Aberrant Portal Hemodynamicsmentioning
confidence: 99%
“…The risk stratification of bleeding is important to identify those who may benefit from a prophylactic treatment with band ligation or sclerotherapy. Up to now, there is no pediatric recommendation for primary prophylaxis with endoscopic ligation, sclerotherapy, or nonspecific beta‐blockers in children …”
Section: Introductionmentioning
confidence: 99%
“…According to recent recommendations for children with PHT based on the Baveno VI consensus, children ‘would be considered’ for surveillance oesophagogastroduodenoscopy (OGD) on the basis of splenomegaly and thrombocytopenia with intention to treat depending on the grade of varices 11. There are two options for endoscopic treatment: endoscopic sclerotherapy (EST) or endoscopic variceal ligation (EVL).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent international survey of specialised paediatric liver units showed that 70% of paediatric centres would perform surveillance OGDs and instigate primary prophylaxis 44. According to current recommendations for children with PHT, based on the Baveno VI consensus, children ‘would be considered’ for surveillance OGD on the basis of hypersplenism with intention to treat depending on endoscopy findings 11. To our knowledge, the decision for a surveillance OGD in children is based on either evidence of splenomegaly on the background of CLD or PVT or radiological evidence of PHT with limited data on the use of predictor models for bleeding risk or presence of varices 45…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation